2009
DOI: 10.1111/j.1745-6622.2009.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Contributions of Brand to Shareholder Value (and How to Maintain or Increase Them)

Abstract: Since 1993 Young & Rubicam has invested over $130 million in collecting and interpreting data on consumers' perceptions of some 44,000 product and service brands in over 50 countries. At the core of Y&R's research effort is the Brand-Asset� Valuator (or "BAV"), a model that converts the firm's hoard of data on global consumer perceptions and behavior patterns into assessments of brand strength and value. When combined with the findings of independent research by academics in marketing and finance (using Compus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
2
7
0
4
Order By: Relevance
“…Respondents similarly noted the aesthetic appeal of other brands that they perceived to be cool across a range of industries from apparel to magazines: "I am very impressed by the design and layout of the magazine (Wired), and I keep each issue to reference for when I am doing graphic design myself." The theme that cool brands have aesthetic appeal is consistent with prior attempts to measure coolness in clothing and technological products (Bruun et al 2016;Runyan et al 2013;Sundar et al 2014 This notion that cool brands are energetic is consistent with the "Brand Energy" construct used by the Brand Asset Valuator (BAV) system of assessing brand strength (Gerzema, Lebar and Rivers 2009). Although some researchers have suggested that coolness is associated with similar traits, including youth (O'Donnell and Wardlow 2000; Runyan et al 2013), hedonism (Pountain and Robins 2000), and "sexual permissiveness" (Bird and Tapp 2008), prior research on coolness has rarely discussed being energetic as a characteristic of cool brands.…”
Section: Themes In the Qualitative Datasupporting
confidence: 70%
“…Respondents similarly noted the aesthetic appeal of other brands that they perceived to be cool across a range of industries from apparel to magazines: "I am very impressed by the design and layout of the magazine (Wired), and I keep each issue to reference for when I am doing graphic design myself." The theme that cool brands have aesthetic appeal is consistent with prior attempts to measure coolness in clothing and technological products (Bruun et al 2016;Runyan et al 2013;Sundar et al 2014 This notion that cool brands are energetic is consistent with the "Brand Energy" construct used by the Brand Asset Valuator (BAV) system of assessing brand strength (Gerzema, Lebar and Rivers 2009). Although some researchers have suggested that coolness is associated with similar traits, including youth (O'Donnell and Wardlow 2000; Runyan et al 2013), hedonism (Pountain and Robins 2000), and "sexual permissiveness" (Bird and Tapp 2008), prior research on coolness has rarely discussed being energetic as a characteristic of cool brands.…”
Section: Themes In the Qualitative Datasupporting
confidence: 70%
“…The first two pillars, energised differentiation and relevance form "brand strength" which is an indicator of future growth value. Conversely, esteem and knowledge, are proxies for current operating value that together determine "brand stature" (Gerzema, Lebar & Rivers, 2009). Millward Brown Optimor, the "Brand Dynamics" index, employs an economic method of brand valuation based on the brand's ability to create demand.…”
Section: Brand Equity Measurement Models: Academic and Industrymentioning
confidence: 98%
“…Cilj upravljanja markom je kreiranje marki lidera, koje imaju maksimalnu vrednost i koje utiču na maksimiranje vrednosti za akcionare (vrednosti preduzeća). Vrednost marke je maksimalna kada su (a) snaga i ugled marke dostigli svoje maksimalne vrednosti (gornji levi kvadrant u matrici na slici 6), a pri tome je (b) snaga marke veća od njenog ugleda (Gerzema, Lebar & Rivers 2009). Stručnjaci i saradnici grupe Young and Rubicam su čak i definisali karakteristike koje marka treba da ima kako bi se održala na visoko konkurentskom tržištu 12 .…”
Section: Bav Metodologija Youngandrubicam Grupeunclassified
“…Fokusiranje na povećanje energetske diferenciranosti može omogućiti "podmlađivanje" (oporavak i nastavak životnog ciklusa i potencijalni rast nakon ulaska u fazu opadanja: slika 6) i ponovni uspeh marki sa dobro utvrđenom pozicijom, što se već desilo markama kao što su: Puma, Adidas, Converse, Gucci, Burberry, Cadillac. U slučaju marke Dove to je ostvareno angažovanjem u kulturalnoj debati sa potrošačima o redefinisanju društvene percepcije lepote (Gerzema, Lebar & Rivers 2009).…”
Section: Bav Metodologija Youngandrubicam Grupeunclassified
See 1 more Smart Citation